DIRECTION CHANGE DAN STERILISASI JALUR BUSWAY: SEBAGAI SOLUSI ALTERNATIF MENGURANGI ANGKA KECELAKAAN DAN MENERTIBKAN LALU LINTAS DI JALUR BUSWAY - Amalia, Putri; Y., Yusalina; N., Nurlela; Febriyadi, Fajar; Prabowo, Putra Agung (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
TransJakarta Bus is a Bus Rapid Transit or bus rapid transport system, which accommodates users of all groups. This bus is one of the common vehicle contributing to accidents on the road of jakarta. Based on data from Jakarta Provincial Government, in 2012 the accidents related to TransJakarta bus have increased significantly from previous year and the figures seem to be ascending from year to year. The accident occurred due to the number of vehicles, in particular, motorists grab into TransJakarta lane. This shows that the awareness of motorists to obey traffic rules and order are poor. Therefore, a solution is needed to reduce the accidents. One of the solutions is to maximize the sterilization and program direction change. Sterilization is an attempt to sterilize the general motorist who get into TransJakarta lane. The program is a Direction Change that change of direction between TransJakarta buses with others vehicles that initially the direction into the opposite direction, or commonly known as contraflow. The program aims to curb the riders and decrease the number of accidents that occur on the TransJakarta lane.